2016
DOI: 10.11138/orl/2016.9.1s.001
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Correlation Between the Facial Biotype and the Inclination of the Upper Canine Cusp Axis to the Occlusal Plane

Abstract: Permanent maxillary canines are the second most frequently impacted teeth and the prevalence of this clinical condition is estimated to be 1-2% in the general population (1). Females are twice as frequently affected (1.17%) as males (0.51%) (2). This atypical limited eruption is most likely due to an extended tooth development period and to a long, difficult path of eruption because of anatomic limitations (3). Palatally displaced canines are three times more frequent than the buccal displacements (2). There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It has been recently suggested that maxillary impacted canines and facial biotype are correlated, 7 and that the impacted canines in hyperdivergent subjects may have a better prognosis. 8 In our opinion, the facial biotype should be taken into account in patients with impacted canines not only for diagnosis but also for treatment planning. We are aware that further longitudinal research is necessary to confirm these relationships.…”
mentioning
confidence: 99%
“…It has been recently suggested that maxillary impacted canines and facial biotype are correlated, 7 and that the impacted canines in hyperdivergent subjects may have a better prognosis. 8 In our opinion, the facial biotype should be taken into account in patients with impacted canines not only for diagnosis but also for treatment planning. We are aware that further longitudinal research is necessary to confirm these relationships.…”
mentioning
confidence: 99%